Countermovement jump variables not tensiomyography can distinguish between sprint and endurance focused track cyclists - Lewis, D. M.; Young, B. W.; Knapstein, L.; Lavender, A.; Talpey, W. S. (Biology of Sport, 2022)
This study investigated the reliability and discriminative ability of tensiomyography and countermovement jump variables as measures of a muscles contractile properties in a cohort of elite endurance and sprint track cyclists. Tensiomyography was performed on the vastus lateralis (VL) and rectus femoris (RF) muscles in sprint track cyclists (N = 8) and endurance track cyclists (N = 8). Additionally, the participants completed a countermovement jump on a force plate. Tensiomyography measurements obtained from the RF displayed greater reliability (ICC = 0.879-0.997) than VL (ICC = 0.746-0.970). Radial muscle belly displacement (Dm), contraction time (Tc) and delay time (Td) demonstrated the most reliable TMG measurements. Only two variables displayed acceptable coefficient of variation (RF Td = 8.89, VL Td = 6.88), other variables presented as unacceptable. The TMG variables were unable to discriminate between endurance and sprint track cyclists whilst the CMJ variables could. Due to the high variability in measurements and its inability to distinguish between sprint and endurance based track cyclists TMG should be used cautiously in this athlete population and if available the CMJ is a more appropriate assessment of leg muscle function.